2022
DOI: 10.21203/rs.3.rs-1451568/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Synthesis, characterization and computational studies of 2-amino-4-substituted thiazoles, their divalent nickel and cobalt complexes and molecular docking studies of their ligands as potent μ-opioid receptor agonists

Abstract: In this study, some 2-amino-4-substituted thiazole derivatives (TH1-TH5) and ligands (L1H and L2H) were synthesized from the reaction of TH1 and TH3 with 2-hydroxybenzaldehyde which were complexed with divalent nickel and cobalt chloride salts to yield complexes: Ni(L1H)2, Co(L1H)2, Ni(L2H)2 and Co(L2H)2. The structure of the compounds was established on the basis of analytical and spectral (1H NMR, 13C NMR and FTIR) data. Computational studies of the derivatives and molecular docking of the ligands were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…As a red colour is predominantly observed, destabilization dominates in these complexes. Previous studies of Ni and Zn complexes have shown a tendency towards square planar for the former, and octahedral and square pyramidal geometries for the latter (Sarıkavaklı et al, 2022). Two-dimensional NCI can be identified by observing well defined troughs for reduced density gradients (RDG) of close to zero for the loci in space.…”
Section: Computational Studies Non-covalent-interactions (Nci)mentioning
confidence: 99%
“…As a red colour is predominantly observed, destabilization dominates in these complexes. Previous studies of Ni and Zn complexes have shown a tendency towards square planar for the former, and octahedral and square pyramidal geometries for the latter (Sarıkavaklı et al, 2022). Two-dimensional NCI can be identified by observing well defined troughs for reduced density gradients (RDG) of close to zero for the loci in space.…”
Section: Computational Studies Non-covalent-interactions (Nci)mentioning
confidence: 99%